FAUST – VIII. The protostellar disc of VLA 1623–2417W and its streamers imaged by ALMA. Issue 2 (11th April 2023) - Mercimek, S; Podio, L; Codella, C; Chahine, L; López-Sepulcre, A; Ohashi, S; Loinard, L; Johnstone, D; Menard, F; Cuello, N; Caselli, P; Zamponi, J; et al.
ABSTRACT: More than 50 per cent of solar-mass stars form in multiple systems. It is therefore crucial to investigate how multiplicity affects the star and planet formation processes at the protostellar stage. We report continuum and C 18 O (2–1) observations of the VLA 1623–2417 protostellar system at 50 au angular resolution as part of the ALMA (Atacama Large Millimeter/submillimeter Array) Large Program FAUST. The 1.3 mm continuum probes the discs of VLA 1623A, B, and W, and the circumbinary disc of the A1 + A2 binary. The C 18 O emission reveals, for the first time, the gas in the disc envelope of VLA 1623W. We estimate the dynamical mass of VLA 1623W, M dyn = 0.45 ± 0.08 M⊙, and the mass of its disc, M disc ∼ 6 × 10 −3 M⊙ . C 18 O also reveals streamers that extend up to 1000 au, spatially and kinematically connecting the envelope and outflow cavities of the A1 + A2 + B system with the disc of VLA 1623W. The presence of the streamers, as well as the spatial (∼1300 au) and velocity (∼2.2 km s −1 ) offsets of VLA 1623W, suggests that either sources W and A + B formed in different cores, interacting between them, or source W has been ejected from the VLA 1623 multiple system during its formation. In the latter case, the streamers may funnel material from the envelope and cavities of VLA 1623AB on to VLA 1623W, thus concurring to set its final mass and chemical content.